Inversion of the conical Radon transform with vertices on a surface of revolution arising in an application of a Compton camera. (19th April 2017) - Moon, Sunghwan
Abstract: A Compton camera has been introduced for use in single photon emission computed tomography to improve the low efficiency of a conventional gamma camera. In general, a Compton camera brings about the conical Radon transform. Here we consider a conical Radon transform with the vertices on a rotation symmetric set with respect to a coordinate axis. We show that this conical Radon transform can be decomposed into two transforms: the spherical sectional transform and the weighted fan beam transform. After finding inversion formulas for these two transforms, we provide an inversion formula for the conical Radon transform.